PENGUKURAN PERMANENT EARNINGS PADA HUBUNGAN DENGAN KEBIJAKAN DIVIDEND PERUSAHAAN : REVIEW PENELITIAN - Wahyu Manuhara Putra (Universitas Muhammadiyah Yogyakarta, Indonesia, 2008)
Corporate earnings divided into a permanent component of earnings and transitory earnings will be very useful in estimating the future value of the company, that will be useful in decision making stock return. Be more relevant for investors and financial analysts in analyzing the earnings based on the permanent and transitory earnings. On permanent earnings will be more focused to get the gain from investments. One focus of research is based on this component is to test the relationship with the earnings dividend payment policy. Based on several studies obtained different results concerning the relationship with the permanent earnings dividend policy. Research that focuses on permanent earnings using two approaches to determine the accuracy of the proxy of permanent earnings. Determination of permanent earnings through the stock price and the latter by using the accounting profit.